Capsular Genotype and Lipooligosaccharide Class Associated Genomic Characterizations of Campylobacter jejuni Isolates From Food Animals in China - Zang, Xiaoqi; Lv, Hongyue; Tang, Haiyan; Jiao, Xinan; Huang, Jinlin (Frontiers in Microbiology, 2021)
Campylobacter jejuni (C. jejuni) is the leading causative agent of gastroenteritis and Guillain–Barré syndrome (GBS). Capsular polysaccharide (CPS) and lipooligosaccharide (LOS) contribute to the susceptibility of campylobacteriosis, which have been concern the major evaluation indicators of C. jejuni isolates from clinical patients. As a foodborne disease, food animal plays a primary role in the infection of campylobacteriosis. To assess the pathogenic characterizations of C. jejuni isolates from various ecological origins, 1609 isolates sampled from 2005 to 2019 in China were analyzed using capsular genotyping. Strains from cattle and poultry were further characterized by LOS classification and multilocus sequence typing (MLST), compared with the isolates from human patients worldwide with enteritis and GBS. Results showed that the disease associated capsular genotypes and LOS classes over-represented in human isolates were also dominant in animal isolates, especially cattle isolates. Based on the same disease associated capsular genotype, more LOS class types were represented by food animal isolates than human disease isolates. Importantly, high-risk lineages CC-22, CC-464, and CC-21 were found dominated in human isolates with GBS worldwide, which were also represented in the food animal isolates with disease associated capsular types, suggesting a possibility of clonal spread of isolates across different regions and hosts. This is the first study providing genetic evidence for food animal isolates of particular capsular genotypes harbor similar pathogenic characteristics to human clinical isolates. Collective efforts for campylobacteriosis hazard control need to be focused on the zoonotic pathogenicity of animal isolates, along the food chain “from farm to table.”